An Overview of Social Support and Resilience among Volcanic Eruption Survivors - Salmareta Tukan, Kristiany Vannia; Benu, Juliana Marlin Yustrianti; Ratu, Feronika (Universitas Nusa Cendana, 2025)
This study explores the theoretical framework of social support and resilience among survivors of the Lewotobi Laki-Laki volcanic eruption. Given the psychological and emotional challenges faced by survivors in the aftermath of a disaster, social support plays a vital role in recovery. The proposed hypothesis suggests that stronger social support from sources such as family, friends, and the community enhances resilience. A quantitative method was employed through surveys to assess both the level of social support received and the strength of the survivors. The results indicate a positive correlation between social support and resilience; survivors who received greater support demonstrated higher levels of resilience. These findings underscore the significance of community-based support systems in facilitating individuals' recovery from traumatic experiences and rebuilding their lives after natural disasters.